Arbetsterapeuters resonemang om livsstilsbalans hos personer inom psykiatrisk öppenvård - Arenvall, Sofia (2015)
The purpose of the study was to describe occupational therapists reasoning about lifestyle balance among people in psychiatric care. The writer used a qualitative design and interviewed five occupational therapists working in psychiatric care in northern Sweden, using a semi structured interview guide. The data was analysed using qualitative content analysis. The results generated three main categories: “Having balance”, “Finding motivation” and “Supporting change”. The occupational therapists reasoned that personal economy was an important part of having balance. Further, the occupational therapists reasoned about group activities as a source for motivation. Reasoning was also about group activities as a motivation for living a healthier lifestyle. Encouraging personal planning was reasoned as one way to support lifestyle changes. Implications for further research are the need for knowing how occupational therapists can support participation in the society for people in psychiatric care, which is an important presumption of lifestyle balance. Validerat; 20150605 (global_studentproject_submitter)